Development and validation of a novel RP-HPLC method for determination of Remdesivir: Investigation of the greenness for the proposed method - Karthika Paul; B.H. Jaswanth Gowda; R.S. Chandan (Results in Chemistry)
Remdesivir, a nucleotide prodrug of an adenosine analogue, exhibits antiviral activity against SARS-CoV-2 by binding to the viral RNA-dependent polymerase and disrupting viral replication. Given its frequent analysis in pharmaceutical QC laboratories, particularly in raw materialsand drug productthe concerns arise regarding self-toxicity, necessitating analysis in toxicological centers for biological fluids. In the context of the growing global philosophy of Green Analytical Chemistry, this study focuses on assessing the greenness of RP-HPLC methods for remdesivir analysis in raw materials. The choice of HPLC methods arises from their known reproducibility, reliability, and widespread availability in quality control. The mobile phase used for the proposed method was methanol: acetonitrile: water in the ratio 10:10:80 (v/v/v) with a flow rate of 1 mL/min and a retention time of 2.2 min. The developed method achieved a LOD of 0.02 μg/mL and LOQ of 0.06 μg/mL, confirming the methodis high sensitivity and suitability for precise quantification of RDV. The study employed commonly used metric systems, for greenness evaluation, the Analytical Eco-Scale and Analytical Greenness. The comparative analysis identifies the Analytical Eco-Scale score of 79 and AGREE value of 0.78 as indicative of the greenest chromatographic method for remdesivir analysis in raw materials. Notably, the National Environmental Methods Index tool exhibits limited performance compared to other metric systems, precluding its standalone use The study concludes that the proposed RP-HPLC methods offer effective greenness with reduced time making it suitable for routine use.